Long-term growth prospects for the Russian economy - Roland Beck; Annette Kamps; Elitza Mileva (European Central Bank (ECB), 2007)
This paper provides an assessment of Russia's long-term growth prospects. In particular, it addresses the question of the medium- and long-term sustainability of the country's currently high growth rates. Starting from the notion that Russia's fast economic expansion in recent years has benefited from a number of singular factors such as the unprecedented rise in oil prices, the paper presents new evidence on Russia's oil price dependency using a Vector Error Correction Model (VECM) framework. The findings indicate that the positive impact of rising oil prices on Russia's GDP growth has increased in recent years, but tends to be buffered by an appreciation of the real effective exchange rate which is stimulating imports. Additionally, there is empirical confirmation that growth in the service sector – a symptom usually associated with the Dutch disease phenomenon – is mainly a result of the transition process. Finally, the paper provides an overview of the relevant factors that are likely to affect Russia's growth performance in the future.
Keywords: O43; O47; O51; O11; O14; 330; Russia; economic growth.; Wirtschaftswachstum; Russland